More than meets the eye : an introduction to media studies - Burton, Graeme (E. Arnold : Distributed in the USA by Routledge, Chapman and Hall, 1990)
An introduction to media studies covering such areas as media institutions, analyses of media products and messages, and a study of the media's effect on audiences.